Advancements in High-Frequency Antenna Design: Integrating Photonic Crystals for Next-Generation Communication Technologies - Bagheri, Nila (2024)
Central to this study is the introduction of a pioneering photonic crystal-based microstrip patch antenna array with high gain. Engineered to meet the demands of evolving wireless communication technologies, this novel antenna system leverages Photonic Band Gap (PBG) structures. A fractal microstrip patch antenna, operating within the E-W-F band, is designed and simulated using the High-Frequency Structure Simulation (HFSS) software. With an operational frequency spanning 60.15 GHz to 120 GHz and a resonant band at 64.80 GHz, the antenna achieves a peak gain of 10.50 dBi within the obtained bandwidth. In this study, we selected Rogers RT/Duroid 5880 as the substrate material for our antenna, capitalizing on its unique properties to achieve superior functionality in high-frequency applications. One of the advantages of RT/Duroid 5880 is its exceptionally low dielectric constant (Ɛr = 2.2). This property is paramount for high-frequency antennas, as a lower dielectric constant facilitates improved signal propagation characteristics. The result is reduced signal loss and enhanced impedance matching, contributing to the overall efficiency of the antenna. The mechanical machinability of RT/Duroid substrates, including RT/Duroid 5880, adds another layer of advantage. The material can be easily cut, sheared, and machined to shape, streamlining the manufacturing process, and allowing for precise customization of the antenna design. In addition, by creating air hole in substrate reduce the dielectric constant, the introduction of air holes can decrease the effective dielectric constant of the material. As a lower dielectric constant results in a slower wave propagation speed, a reduction wavelength and a more compact antenna design may result. The presence of air holes or a photonic crystal structure can modify the electromagnetic properties of the substrate, potentially leading to enhanced bandwidth characteristics of broadband antennas.